Circuit design considerations for implantable devices. - Cong, Peng (River Publishers series in electronic materials and devices., 2017)
"Implantable devices are a unique area for circuit designers. A comprehensive understanding of design trade-offs at the system level is important to ensure device success. Circuit Design Considerations for Implantable Devices provides knowledge to CMOS circuit designers with limited biomedical background to understand design challenges and trade-offs for implantable devices, especially neural interfacing."--